Assistance In Learning Basic Early Childhood Motion Skills For Early Childhood Teachers In Pesisir Selatan Regency - Risky Syahputra; Syahrial Bakhtiar; Oktarifaldi Oktarifaldi; Willadi Rasyid; Lucy Pratama Putri (Universitas Negeri Padang Press, Pusat Kajian Pendidikan Olahraga, Kesehatan dan Rekreasi, Fakultas Ilmu Keolahragaan, Univeristas Negeri Padang., 2020)
Based on observations, it was found that almost all teachers and PAUD educators in Pesisir Selatan district did not have the insight and skills in realizing basic motion learning. Permendiknas No. 58 of 2009 is the basis of Early Childhood Education Standards (PAUD) which have been explained in depth all aspects, contents, goals and objectives of the government in PAUD, but the reality is still far from the target. Met the implementation of PAUD in Indonesia, including in the Pesisir Selatan district, prioritizing academic content such as writing, counting and reading, looks poor providing opportunities for active play and physical activity for children. Based on research, basic motion cannot develop naturally but must be taught correctly and continuously. Community service activities for partners aim to: (a) know the importance of basic motion, (b) have skills in practicing basic motion of early childhood, (c) be able to use instruments and know the level of basic motion skills of children. The method used uses the principle that every innovation received by PAUD teachers through PIE (Preparation, Implementation and Evaluation). Submission of innovations to Partners taken through the stages of explanation, discussion, practice and evaluation and assistance in learning. . The results of the training obtained by partners as participants can be described as follows: (a) Having insight and understanding of the importance of basic movement skills, (b) having experience in practicing basic motion skills, (c) knowing and having the ability to use instruments and knowing the level of motion skills basic child.